The Comic Art of Jane Austen: A New Approach Vs. The Title of Pride and Prejudice - Priydarshi, Ashok Kumar (Journal of Advanced Research in English & Education; Vol 10 No 3 (2025): Journal of Advanced Research in English and Education, 2025)
Jane Austenâ€™s â€œPride and Prejudiceâ€ is a title that encapsulates the central thematic conflicts of the novel. However, examining it through the lens of Austenâ€™s comic art reveals a deeper understanding of how these concepts are portrayed and subverted. This article argues that Austenâ€™s use of wit, irony, and satire is not merely a backdrop but a crucial element in conveying the nuances of pride and prejudice. By analyzing specific instances of comic portrayal, we can see how these traits are both ridiculed and humanized, revealing their inherent absurdity and the possibility of transformation. Austenâ€™s comic art serves to highlight the social and personal consequences of these f laws, while simultaneously providing a path towards self-awareness and redemption. The title itself becomes a canvas for Austenâ€™s comedic genius, as she uses humor to expose the follies of her characters and the societal expectations that perpetuate these prejudices. We will explore how Austenâ€™s comic devices, such as irony, hyperbole, and comic misunderstandings, are used to dissect and ultimately resolve the conflicts embodied in the title. This approach offers a fresh perspective on the novel, revealing how Austenâ€™s comedic genius is integral to the t itleâ€™s thematic resonance, enriching our appreciation of her enduring literary achievement.